Penanaman Nilai Moral Pancasila di Lingkungan Sekolah Berbasis Agama terhadap Prinsip Kebhinekaan - Adrian Daulay; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Imel Simbolon; Marlina Elisa Marpaung; Sarah Miranda Gultom (Departement of Mathematics Education, 2024)
This research discusses religious diversity which is a natural part of the modern school environment. Each school member adheres to a different religion, has different traditions, and celebrates different religious holidays. Therefore, it is very important for schools to create an atmosphere where everyone, regardless of religion or belief, can feel welcome. Islam, Catholicism, Christianity, Hinduism, Buddhism and Confucianism are some of the religions widely practiced in Indonesia. The research aims to find out how students' attitudes respect diversity by using quantitative research methods by collecting data through questionnaires given to grade 8 students at SMP Negeri 14 Medan with a total of 26 respondents. This data will be analyzed statistically to determine students' understanding of religious diversity. As a pluralistic nation, Indonesia will certainly face small conflicts and even major betrayals. The disintegration of the nation will certainly have an impact if this disease is not treated. For this reason, it is necessary to instill an understanding of religious pluralism without conflict in students from childhood.